Correlation between History Early Breastfeeding Initiation and Exclusive Breastfeeding among Mothers of Infants Aged - Ni Wayan Novi Hardiyani; Ni Made Dwi Mahayati; Gusti Ayu Eka Utarini (WMJ (Warmadewa Medical Journal))
This study investigates the relationship between early initiation of breastfeeding (EIBF) and exclusive breastfeeding to mothers in the Banjarangkan II Public Health Center, Regional Technical Implementation Unit (RTIU). This study employs the correlative analytical method of cross-sectional design, utilizing a retrospective approach. This study lasted from February to April 2024. The random proportional sample method consists of 58 individuals. We collected data through questionnaires and used the Fisher exact test for data analysis. The results of the study showed that the majority (89.7%) of mothers of babies aged 7–12 months had EIBFs, and most (82.8%) had exclusive breastfeeding. Studies show that mothers who perform EIBF in the Banjarangkan II Public Health Center's Regional Technical Implementation Unit work area and have babies aged 7–12 months are more likely to provide breast milk as the only source of nutrition for babies, often called exclusive breastfeeding. The results indicate a correlation between the history of EIBF and exclusive breastfeeding among mothers, with a contingency coefficient value of 0.597. To implement EIBF, midwives must continue to promote pregnant mothers’ health.